Outcome of Nonsurgical Management of Extra-Abdominal, Trunk, and Abdominal Wall Desmoid-Type Fibromatosis: A Population-Based Study in the Netherlands. (21st June 2018) - van Broekhoven, Danique L. M.; Verschoor, Arie J.; van Dalen, Thijs; Grünhagen, Dirk J.; den Bakker, Michael A.; Gelderblom, Hans; Bovee, Judith V. M. G.; Haas, Rick L. M.; Bonenkamp, Han J.; van Coevorden, Frits; ten Oever, Diederik; van der Graaf, Winette T. A.; et al.
Abstract : Introduction . Nonsurgical management of patients with desmoid-type fibromatosis (DF) is increasing. This study tries to provide insight on type, usage, and outcome of first-line nonsurgical management strategies. Patients and Methods . From the Dutch Pathology Registry (PALGA), patients with extra-abdominal or trunk/abdominal wall DF, diagnosed between 1993 and 2013, were identified. First-line treatment was analyzed. Best response (BR) using RECIST criteria from start of treatment/surveillance until change of treatment or last follow-up was analyzed. Results . Ninety-one of the 1141 identified patients had first-line nonsurgical management. The percentage of patients treated nonsurgically increased from 0.6% in 1993–1998 to 12.8% in 2009–2013. Thirty-seven patients had surveillance (41%), 35 radiotherapy (38%), and 19 systemic treatment (21%). BR for surveillance was complete response (CR) in 2/37, partial response (PR) in 4/37, stable disease (SD) in 21/37, progressive disease (PD) in 5/37, and unknown in 5/37 patients. BR for radiotherapy was CR in 4/35, PR in 11/35, SD in 16/35, and unknown in 4/35. BR for systemic treatment was CR in 1/19, PR in 1/19, SD in 10/19, PD in 2/19, and unknown in 5/19. Totally, 91% of patients did not progress. Discussion . Given the low percentage (9%) of PD of nonsurgical management, these data can be used in shared decision making with the patient regarding optimal treatment.